Association of the Ratio of Second to Fourth Digit Length and Phthalate Exposure With Sexual Function in Japanese Men Seeking Fertility Treatment - Kazumitsu Yamasaki; Masahiro Uchida; Yuki Mizuno; Teruaki Iwamoto; Shoko Konishi (American Journal of Men's Health)
Sexual dysfunction, which is increasingly recognized as a cause of male infertility, may be influenced by environmental factors such as phthalic acid diesters (phthalates) and prenatal androgen exposure. This study aimed to investigate the association between male sexual function and recent exposure to phthalates and prenatal testosterone. The cross-sectional study included 177 males seeking fertility treatment. The index-to-ring-finger length ratio (2D:4D) was calculated as a measure of prenatal androgen exposure. To evaluate recent phthalate exposure, urinary concentrations of seven phthalate metabolites were measured. Their associations with International Index of Erectile Function (IIEF) scores were analyzed using generalized linear models. One standard deviation increase of mono-methyl phthalate was negatively associated with IIEF domains A (erectile function; exponentiated coefficient, 0.95; exponentiated 95% confidence interval, CI, [0.91, 0.98]) and D (intercourse satisfaction; exponentiated coefficient, 0.91; exponentiated [0.85, 0.97]). While mono-butyl phthalate was positively associated with domain A, mono-ethyl phthalate, monobenzyl phthalate, and the molar sum of di (2-ethylhexyl) phthalate metabolites showed no significant association with IIEF domain scores. When the serum testosterone concentration was included as an exposure variable, the overall association between urinary phthalates and IIEF domain scores remained similar. The left- and right-hand 2D:4D ratios did not show significant associations with any IIEF domain scores. Recent phthalate exposure may affect male sexual function by decreasing testosterone levels and other potential mechanisms.